VALIDATION OF THE SELECTION OF GENOTYPES OF SUGAR-CANE FOR THE STATE OF PARANÁ - ZAMBON, José Luis Camargo (Scientia Agraria, 2001)
Experiments were done with genotypes of sugar-cane of the series RB84, RB85 and RB89, in 17 places of the State of Paraná, that is bordering area because the climatic characteristics, to the South, for the cultivation of the sugar-cane. The appraised experiments are of the Experimental Phase (FE) of the process of obtaining new varieties of the Programa Cana-de-açúcar of RIDESA - PR. With the objective of validating the method used in the evaluation of new sugar-cane genotype, they were identified those with good production potential, appraised the adaptability and stability of them and compared with the series three RB. For the adaptability and stability was used the method of Eberhat and Russel and the identification and comparison of the genotype was made by test of averages, coefficient of variation among the averages of the different places, superiority frequency from the patterns, as well as histograms for frequency strip for each series. It was used the characteristics of TCH (tons of sugar-cane culm by hectare) and TPH (tons of POL for hectare) as indicative for the choice of the best genotype. For the used method, it is possible the identification of superior genotype in the three series. The heterogeneity of the results exhibit the need of the evaluation to be done in the largest number of possible locality. The interaction of the genotype with the ambient presents production increase with the ambient improvement, with different intensity among them, by the variation in the response of the genotype to this interaction. When compared the three series, although some genotype of different series have the same progenitors, they show different behavior and for RB89 presented medium values of TCH and smaller TPH, even so, as the other series possesses promising genotype, that is superiors to the patterns, with cultivation potential in the Stale of Paraná, demonstrating the validity of the methodology used in its improvement.